Labor costs and localization in global value chains: Comparative analysis and conclusions for Poland - Magdalena Kapela (Foundations of Management, 2019)
Labor costs in Poland are relatively low in comparison to other European Union (EU) countries. After long period of functioning Poland in closed economy, conditions significantly weakened the level of its competitiveness in the international market. When the boards were opened in 1989, it became clear that cheap work force was one of the most important factors to attract foreign investments. At the same time, globalization and internationalization of production created opportunity for entrepreneurs to establish global value chains. Participation in global value chain (GVC) of Poland can extend international trade and increase gross domestic product (GDP). On the other hand, low wages attract investments in low-technology industries and, moreover, place Poland in the middle of value chains, where semi-products are assembled and new value added is exiguous. The aim of the article is: 1) to present polish participation in global value chain, 2) to analyze how much low labor costs contribute to degree of share in global value chain, and 3) to show how level of labor costs contribute to position in value chain and how does it influence on benefits from participating in GVC. In the article, the quantitative and qualitative assessment of Eurostat (European statistic) and Organisation for Economic Cooperation and Development (OECD) statistics data and research on labor costs carried out in Poland were analyzed. The research tools include a critical analysis of literature and descriptive analytical method. More than 50% of polish exports takes place within the global value chains. Low labor costs attract investors to allocate part of their production in Poland. Nevertheless, great part of export constitutes semi-products that do not create new value added so benefits from participation in GVC are not so considerable as expected. It is desirable to shift Poland toward beginning or the end of value chains, where profits are higher.
Keywords: F16; F43; J38; 650; labor costs; wages; global value chains; value added; value added in trade; Poland